Trilingual Education: Main Items and Outcomes for Kazakhstani Youth - Ainash , Ainash; Chaklikova, Assel; Shayakhmetova, Dana; Yessentemirova, Aigul (International Journal of Psychosocial Rehabilitation, 2020)
The article is devoted to the aspect of developing trilingual competence of Kazakhstani students of linguistic and non-linguistic specialties. The authors present the study with duration of one academic year. The study results presented demonstrate the effective impact of techniques chosen in order to develop the trilingual competence. The aim of developing such a competency is to prepare students for communication and life in trilingual and polycultural modern world, to lead the country to prosperity and remember the dignity. The authors also try to underline the importance of trilingual competence which is significant today in modern Kazakhstan. The trilingual competence is the basis for learners of any specialty. Developing the chosen competence students become polycultural. Aside from that students due to English knowledge as the international language are ready to communicate in global process of constant integration in all spheres. The techniques that were used in the experiment demonstrated the effectiveness according to the survey that has been taken in the end of the academic year to reveal the results.